Managing Kubernetes operating Kubernetes clusters in the real world - Burns, Brendan 1976-; Tracey, Craig (O'Reilly Media, 2018)
"While Kubernetes has greatly simplified the task of deploying containerized applications, managing this orchestration framework on a daily basis can still be a complex undertaking. With this practical book, site reliability and DevOps engineers will learn how to build, operate, manage, and upgrade a Kubernetes cluster--whether it resides on cloud infrastructure or on-premises."--